A Comparison of Time-Varying Online Price and Price Dispersion between Multichannel and Dotcom Dvd Retailers - Xing, X. L. (Institutional Knowledge at Singapore Management University, 2006)
We compare price differences and market dynamics between two types of online retailers: online branches of multichannel retailers (OBMCRs) and pure Internet retailers (Dotcoms), based on a set of panel data collected from the DVD market. We find that (i) OBMCRs charge higher prices than Dotcoms, (ii) prices go up with time for both OBMCRs and Dotcoms, and (iii) prices of Dotcoms go up faster than those of OBMCRs.We also find that price dispersions of OBMCRs and Dotcoms are significantly different and the difference decreases with time. Our results show that although the two types of retailers have different price levels and different price dispersions at the beginning, such differences are getting smaller over time, implying that the two types of retailers will have similar pricing behavior in the long run. However, persistent price dispersion among all retailers exists in the market, even over a long period.